Influence of leaf extract additives on performance, emission and combustion characteristics of biodiesel operated DI diesel engine - Silambarasan Rajendran; Ravikumar Venkatachalam; Balu Pandian; Sivashankar Arumugam (Discover Sustainability)
Abstract The increasing demand for sustainable and environmentally friendly fuels has driven research on biodiesel blends' combustion characteristics, emissions, and oxidative stability. This study underscore the significance of incorporating leaf extract additives into macauba and soybean biodiesel blends. These additives are vital in enhancing combustion characteristics, reducing emissions, improving oxidative stability and evaluating performance indicators. Experimental results indicate that the addition of leaf extract improved Brake Thermal Efficiency (BTE) by 4.2% compared to neat biodiesel. Specific Fuel Consumption (SFC) was reduced by 3.8%, demonstrating improved combustion efficiency. Emission analysis revealed a 12.5% reduction in NOx, a 15.3% decrease in carbon monoxide (CO), and a 10.8% reduction in hydrocarbon (HC) emissions, attributed to enhanced combustion characteristics and improved oxygenation of the fuel. Furthermore, combustion analysis showed a 6.7% increase in peak in-cylinder pressure and a shorter ignition delay. The regression analysis provides insights into the relationships between predictor variables and response variables for each blend, guiding optimal engine performance and emission control strategies. The assessment of oxidative stability highlights the potential of leaf extract additives to enhance the long-term storage and usability of both biodiesel blends.